Treatment of Entropion – A modified Technique: 10.36351/pjo.v36i3.1020 - Qurban, Qirat; Kamil, Zeeshan; Khan, Muhammad Tanweer Hassan (Pakistan Journal of Ophthalmology, 2020)
Purpose: To study the results of a modified technique of Entropion correction at a Tertiary care hospital. Study Design: Quasi experimental study. Place and Duration of Study: Layton Rahmatullah Benevolent Trust (LRBT), a tertiary care teaching Eye hospital, Korangi, Karachi, for a duration of six months, from January 2018 to June 2018. Material and Methods: Patients with senile entropion were included in the study. Patients with recurrent entropion, cicatricial entropion, chronic/acute ocular and adnexal infection were excluded. Three equally spaced double-armed 6–0 vicryl horizontal mattress sutures were used to close the skin and orbicularis muscle of the wound with a bite of the retractors in the center and a 5 mm silicone tube bolster place in the superior loop. Postoperative treatment of antibiotics, anti-inflammatory drugs and topical lubricant eye gel were given. Patients were examined on 11stpost operative day and then weekly interval for up to one month and thereafter every month for up to six months. Results: There were 40 eyes of 30 patients with ages ranging from 50 to 65 years. Twenty (66%) patients had unilateral repair and 10 (33%) had bilateral repair done. No recurrence was seen in 39 (97.5%) eyes at the end six months after surgery. Out of the 40 patients, only 2 (5%) patients complained of heaviness which went away eventually with the disintegration of the external tamponade. Conclusion: This modified technique of entropion repair using skin excision with retractor plication in the wound has a favorable outcome with minimum recurrences and complications.